OC-040 National Survey of Practice of Faecal Microbiota Transplantation for Clostridium Difficile Infection in the United Kingdom. (17th August 2016) - Quraishi, MN; Segal, J; Mullish, B; McCune, V; Hawkey, P; Colville, A; Williams, H; Hart, A; Iqbal, TH
Abstract : Introduction: The National Institute of Health and Care Excellence recommend the use of faecal microbiota transplantation (FMT) for recurrent or refractory Clostridium difficile infection (CDI), as studies have shown it to be a highly effective therapy with a primary cure rate of over 90%. 1 We aimed to conduct a National survey to explore current practice of FMT and the challenges faced by hospitals in setting up this novel treatment strategy. Methods: UK gastroenterologists, microbiologists and infectious disease physicians were invited to take part in a National survey by completing an online questionnaire over a five month period from October 2015. Results: A total of 255 responses were obtained, of which 219 were evaluable. These came from 124 microbiologists/infectious disease clinicians and 95 gastroenterologists. The survey covered 130 independent sites: 112 acute NHS Trusts in England, 9 hospitals in Scotland and 9 hospitals in Wales. Only 28% (36/130) had performed FMT for refractory or recurrent CDI, of which 58% (21/36) of sites had experience of performing FMT for over 1 year, but only 19% (7/36) had treated at least 10 patients. 67% (24/36) made FMT on site while 33% (12/36) obtained FMT from elsewhere to administer at their hospital. Apart from one site that used FMT for refractory ulcerative colitis there were no other indications for its use. Of the 94 independent sites that did not perform FMT for refractory or recurrent CDI, 45% (42/94) believed that they were unable to do it due to lack of facilities, 38% (36/94) did not know where to start, however only 5% (5/94) felt reluctant to do it because of its perceived unpleasantness. Of those sites not performing the procedure, 70% (66/94) suggested that they would be keen to have support in setting up an FMT service for CDI locally. Only 29% (27/94) of the sites that did not perform FMT had referred their patients elsewhere; primarily to Glasgow, Birmingham and Exeter. Conclusion: In the largest National survey done to date exploring the practice of FMT in UK, we have shown that only a quarter of responding sites performed FMT for recurrent or refractory CDI. There are significant challenges faced by hospitals in setting up this service. However, most welcomed support due to unfamiliarity with the perceived logistical hurdles. A central quality controlled and regulated FMT preparation, delivery and support service for the UK may be an efficient model to ensure continued and safe access to this novel treatment strategy for patients in the NHS. Reference: 1 https://www.nice.org.uk/guidance/ipg485 Disclosure of Interest: None Declared